Protective effect of Myrtle (Myrtus communis) on burn induced skin injury - ŞEN, ALİ; YARAT, AYŞEN; ALTURFAN, EBRU IŞIK; ÇETİNEL, ŞULE; AKBAY, TUĞBA (ELSEVIER SCI LTD, 2019)
Thermal skin burns cause local injury as well as triggers acute systemic inflammation response where the imbalance between oxidative and antioxidative system occurs. As an alternative treatment, various medicinal herbs are used to treat burn injuries in many countries. In this study, the possible protective role of oral or topical Myrtle (Myrtus communis L.) treatment against burn-induced damage was investigated. The dorsum of the Wistar Albino rats was shaved and exposed to 90 degrees C water bath in burn group or 25 degrees C water bath in control group for 10 s under ether anesthesia. Myrtle extract was applied 100 mg/kg/day for 2 days either orally or topically. In skin samples; malondialdehyde and glutathione levels, catalase, superoxide dismutase, nitric oxide and tissue factor activities were determined. Skin tissues were also examined by light microscopy. Severe thermal skin bum injury caused a significant decrease in glutathione level, superoxide dismutase, catalase and tissue factor activities as well as nitric oxide level, which was accompanied with significant increases in skin malondialdehyde level. Myrtle treatment reversed all these biochemical indices except topical Myrtle treated group's nitric oxide level, as well as histopathological alterations, which were induced by thermal trauma. Both oral and topical Myrtle extract treatment was found to have protective role in the bum induced oxidative injury, which may be attributed to the potential antioxidant effect of Myrtle. As a conclusion, Myrtle significantly diminishes burn-induced damage in skin. (C) 2019 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Burn; Skin; Myrtle; Oxidative damage; Tissue factor; OXIDATIVE ORGAN DAMAGE; RAT MODEL; ESSENTIAL OIL; ANTIOXIDANT; L.; EXTRACT; BLOOD